Introduction to the cyber ranges - Pandey, Bishwajeet; Ahmad, Shabeer (Electronics engineer) (Boca Raton : Chapman & Hall/CRC Press, 2022)
"Introduction to cyber ranges provides a comprehensive, integrative easy to comprehend overview of different aspects involved in cybersecurity arena. It expands on various concepts like cyber situational awareness, simulation and emulation environments and cybersecurity exercises. It also focuses on detailed analysis and comparison of various existing cyber ranges in military, academic and commercial sectors. It highlights every crucial aspect responsible for developing a deeper insight about the working of the cyber ranges, their architectural design, and their need in the market. It conveys how cyber ranges are complex and effective tools in dealing with advanced cyber threats and attacks. Enhancing the network defences, resilience and efficiency of different components of critical infrastructures are the principal objectives of cyber ranges. They provide simulations of possible cyber-attacks and training on how to thwart such attacks. They are widely used in urban enterprise sectors because they present a sturdy and secure setting for hands-on cyber skills training, advanced cybersecurity education, security testing/training and certification. Features: a comprehensive guide to understanding the complexities involved with cyber ranges and other cybersecurity aspects, substantial theoretical know-how on cyber ranges, their architectural design, along with case studies of existing cyber ranges in leading urban sectors like military, academic and commercial, elucidates the defensive technologies used by various cyber ranges in enhancing the security setups of private and government organizations. The text provides information organized in an accessible format for students in engineering, computer science, information management, professionals, researchers and scientists working in fields of IT, cybersecurity, distributed systems and computer networks"--
OCLC-licensed vendor bibliographic record.
Keywords: Computer networks -- Security measures -- Study and teaching; Classroom learning centers; Activity programs in education; Cyberterrorism -- Simulation methods; COMPUTERS / Computer Engineering; COMPUTERS / Internet / Security; COMPUTERS / Networking / Security